AGENCY THEORY AND OPTIMAL CAPITAL STRUCTURE - MARIA ZENOVIA GRIGORE; VIORICA MIRELA ŞTEFAN-DUICU (Challenges of the Knowledge Society)
In the corporate finance, the agency theory tries to explain the behavior of various agents that intervene in the company’s funding (managers, shareholders and debt holders) and to analyze the impact of these behaviors on the financial structure. Accordingly to the agency theory, the optimal financial structure of the capital results from a compromise between various funding options (equity, debts and hybrid securities) that allow the reconciliation of conflicts of interests between the capital suppliers (shareholders and creditors) and managers. The indebtedness allows shareholders and managers to adhere to same objectives, but causes other conflicts (between managers and shareholders, on the one hand, and creditors, on the other side). The optimal level of indebtedness is the one that allows the minimization of overall agency costs.